Countering Radicalisation of Muslim Community Opinions on the EU Level - Zięba, Aleksandra; Szlachter, Damian (International Studies. Interdisciplinary Political and Cultural Journal, 2015)
The paper explores selected factors influencing the process of radicalisation leading to the use of political violence and terror by the Muslim minorities living in the European Union member states. Internal and external catalysts conditioning this process and methods of their analysis have been presented. The second section examines various counter-radicalisation and de-radicalisation efforts of the EU. The authors analysed the multidimensional European Union policy in the area of counteracting radicalisation for empowering the population and member states in preventing the radicalisation and recruitment to terrorism and emphasising the role of social partners and local authorities. Also, the promotion of good practices for combating radicalisation, developed under the auspices of the multidisciplinary Radicalisation Awareness Network (RAN) is presented.